Asymmetric synthesis of chiral phosphines and arsines promoted by organometallic complexes - Liu, Fengli (2010)
This thesis describes the development of chiral cyclometalated-amine template promoted asymmetric reactions such as the Diels-Alder reaction, hydrophosphination reaction and hydroarsination reaction for the synthesis of chiral phosphine and chiral arsine ligands. Chapter 1 is the general introduction about chiral phosphine and arsine ligands. Chapter 2 describes the Diels-Alder reactions between 3-diphenylphosphinofuran and various vinylphosphine dienophiles in the presence of the organo-platinium complex to give the endo-cycloadducts. Chapter 3 reports the Diels-Alder reaction between 3-diphenylphosphinofuran and DMPP under the promotion of the organo-platinum complex in which the furan acts as the dienophile. Chapter 4 deals with the asymmetric hydrophosphination of diphenylphosphine with pyridine and quinoline complexes in the presence of the organo-palladium complex to generate the optically pure keto- and ester-functionalized chiral P-N bidentate ligands. Chapter 5 presents the asymmetric hydroarsination reactions as a new and alternative technique of preparing chiral As-N bidentate ligands promoted by the organo-palladium complex. Chapter 6 describes the asymmetric hydrophosphination between phosphinoalkynes and phenylmethylphosphine in the presence of the organo-palladium complex to generate the P-chiral diphosphines.